The Right to Privacy in Digital World – Miskolc International Scientific Conference / Pravo na privatnost u digitalnom svijetu – Međunarodna naučna konferencija u Miskolcu - Bobrovský, Dominik (Pregled: časopis za društvena pitanja / Periodical for social issues, 2023)
This text is review of the International scientific conference The Right to Privacy in the Digital Age – in specific terms, which was held in Hungarian Academy of Sciences in Budapest on 1st December 2022